Boundedness of Multidimensional Dunkl-Hausdorff Operators. (10th April 2020) - Daher, Radouan; Saadi, Faouaz
Abstract : In the present paper, we introduce the multidimensional Dunkl-Hausdorff operator ℋ κ and we give simple sufficient conditions so that these operators be bounded on the weighted lebesgue spaces L κ p ℝ n and in the Hardy space H κ 1 ℝ n associated with the Dunkl operators. We also determine the Dunkl-Hausdorff operator ℋ κ ∗ that is adjoint to ℋ κ .